Investigation of surface roughness and choip formation on through hole drilling of mild stell - Nurfatin Syakira Balqis Mohamed Aminuddin (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
In drilling process at the industry, the problem that always emerges is severe waer occur at cutting tool and surface finish on workpiece. This is because of improper selection of cutting paramenter thar affect to cutting tool condition. In this study, the experriment was performed to investigate surface roughness and chip formation on through hole drilling method using ucoated high speed steel (HSS) cutting tool in dry machining condition when dring AISI 1018 mild steel surface rogngess was evaluated on workpiece, where to compare surface roughness condition during the drilling process at various cutting speed